BARRIERS OF BEING ACTIVE: GENDER DIFFERENCES IN YOUNG POPULATION. (April 2021) - Rosselli, Martina; Mascherini, Gabriele; Boddi, Maria; Stefani, Laura; Toncelli, Loira; Galanti, Giorgio; Modesti, Pietro Amedeo
Abstract : Objective: Regardless of any weight change. adopting and maintaining a healthy lifestyle has been shown to lead to meaningful improvements in cardiometabolic risk factors. including fasting insulin. and blood pressure. Although adolescent-specific lifestyle recommendations have been developed. many adolescents do not meet lifestyle behavior recommendations. The study aimed to investigate gender differences in perceived barriers to exercise in a young population. Design and method: A cross-sectional study was conducted among high school students (n = 368). Participants underwent measurements of anthropometric parameters (weight. waist. and hip circumferences). blood pressure. and administration of standardized questionnaire (Barriers to Being Active quiz and Mediterranean Diet Score quiz). Gender differences were assessed with multivariate logistic regression (adjusted for age and BMI). Results: Prevalence of overweight (BMI > 25 kg/m2) was lower among girls than among boys (3.9 % and 8.3%. OR.720; 95% CI 0.645 to 0.803) with no difference in the adherence score of Mediterranean diet (31.4 ± 4.0 and 30.8 ± 4.3. OR 1.036; 95% CI 0.984 to 1.090). The number of perceived barriers to physical activity was higher among girls than among boys (OR 1.519; 95% CI 1.286 to 1.793). Lack of energy for exercise and lack of willpower were the two barriers most frequently reported by girls (see table; n = 368 included in analysis; *adjusted also for age and BMI) Figure. No caption available. Conclusions: Exercise professionals should be aware of the barriers that young girls can face during exercise prescription and be able to contrast them with useful individual strategies. Furthermore, analysis of young people life-style habits can help finding social strategies to promote healthy behaviors.